An adaptive fractional fuzzy sliding mode controlled PSS for transient stability improvement under different system uncertainties. Issue 1 (25th January 2021) - Paital, Shiba R.; Ray, Prakash K.; Mohanty, Soumya R.; Mohanty, Asit
Abstract: An adaptive fractional fuzzy sliding mode controller (AFFSMC) based power system stabilizer (PSS) is proposed for damping out low‐frequency oscillations in single machine infinite bus and multimachine power systems under various operational contingencies. The proposed stabilizer is a combination of adaptive fuzzy control with a fractional order proportional integral derivative controller and sliding mode controller. A fractional sliding surface is adopted which enables the system to remain in the proposed robust sliding surface stably to eliminate the effects of chattering at any initial conditions. In addition, fractional adaptive rules based on fuzzy sets were used for optimal selection of parameters of the controller. Here, the stability issue is addressed through Lyapunov synthesis. Speed deviation and acceleration are considered as input signals to the proposed controller. A comparative analysis of performance indices such as settling time, maximum peak overshoot is presented to demonstrate the advantages of the proposed approach. In addition, stability analysis using Eigen value, integral time absolute error and shape of demerit were also presented to augment the stability study. The simulation results confirm that the proposed AFFSMC‐PSS shows superior robust damping performance as compared to other approaches.